The Sportscomp Erasmus+ Project: Higher Education to Improve Competency in Sports Physiotherapy - Carlo Ramponi; Armi Hirvonen; Mati Arend; Eleni Kapreli; Prof. Dr. Jo Verschueren (International Journal of Sports Physical Therapy)
One of the most important milestones of the International Federation of Sports Physical Therapy (IFSPT), a specialty group of the World Physiotherapy (WP) group, was the creation of the Sports Physiotherapy Competencies and Standards document. This statement, finalized by an international panel of experts almost twenty years ago, under The European Union-funded Sports Physiotherapy for All (SPA) project, describes effective professional behaviours and integrates specific knowledge, skills and attitudes in the context of practice. These competencies provide a basis for policy development, enable quality assurance activities and facilitate individual professional development.